CONTINUOUS DEVELOPMENT TECHNOLOGIES OF METHODOLOGICAL COMPETENCE IN KURASH COACHES: INTERNATIONAL EXPERIENCE AND NATIONAL APPROACHES (Eureka Journal of Education & Learning Technologies, 2026)
This article provides a theoretical and practical analysis of the continuous professional development of wrestling coaches. It emphasizes the necessity of enhancing methodological, pedagogical, and psychological competencies in coaching practice. International experiences (United World Wrestling, NWCA, British Wrestling) are compared with the current opportunities in Uzbekistan. The paper highlights the role of innovative methods, modern information technologies, and certification systems in the process of continuous coach education. The findings contribute to improving the qualifications of wrestling coaches, increasing the effectiveness of athlete preparation, and supporting the development of the national wrestling school.
Keywords: Wrestling sport, coaching competence, continuous education, professional development, innovative methods, certification system.